2017
DOI: 10.1111/ppl.12654
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in embolism resistance and stem anatomy across four sunflower (Helianthus annuus L.) accessions

Abstract: Drought-induced xylem embolism is a key process closely related to plant mortality during extreme drought events. However, this process has been poorly investigated in crop species to date, despite the observed decline of crop productivity under extreme drought conditions. Interspecific variation in hydraulic traits has frequently been reported, but less is known about intraspecific variation in crops. We assessed the intraspecific variability of embolism resistance in four sunflower (Helianthus annuus L.) acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…Given that leaves have a shorter lifespan and are usually exposed to greater variations in water potential, it seems likely that they may exhibit a higher degree of plasticity in vulnerability when compared to stems. When considered in the context of relatively low plasticity of stem vulnerability in sunflower (Stiller & Sperry, 2002;Ahmad et al, 2018), this seems to be the case for this species. Additionally, it is notable that sunflower appears to exhibit a higher degree of vulnerability segmentation than other herbs such as tomato (Skelton et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Given that leaves have a shorter lifespan and are usually exposed to greater variations in water potential, it seems likely that they may exhibit a higher degree of plasticity in vulnerability when compared to stems. When considered in the context of relatively low plasticity of stem vulnerability in sunflower (Stiller & Sperry, 2002;Ahmad et al, 2018), this seems to be the case for this species. Additionally, it is notable that sunflower appears to exhibit a higher degree of vulnerability segmentation than other herbs such as tomato (Skelton et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Analyses in this regard have produced mixed results to date. At the intraspecific level, Corcuera, Cochard, Gil‐Pelegrin, and Notivol () found a correlation between greater hydraulic conductivity and lower embolism resistance in maritime pine, whereas Ahmad et al () showed that sunflower accessions that were more resistant to xylem embolism also transported water more efficiently. The lack of trade‐off between xylem safety and efficiency was further evidenced in Scots pine (Martínez‐Vilalta et al, ) and European beech (Schuldt et al, ), as well as at the interspecific level across a large pool of woody species distributed worldwide (Gleason et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some herbaceous grasses have been found to be more resistant to embolism than previously thought: the xylem pressure inducing a 50% loss of hydraulic conductivity (Ψ 50 ) ranged from −0.5 MPa in reed canary grass (Phallaris arundinacea) to −7.5 MPa in European feather grass (Stipa pennata; Lens et al, 2016). The few estimates of crop Ψ 50 available so far range from −1.6 MPa in rice (Stiller, Lafitte, & Sperry, 2003) to −3 MPa in sunflower (Ahmad et al, 2017), but embolism resistance can vary significantly between different varieties within a crop species (Ahmad et al, 2017). The limited number of studies investigating crop hydraulics were carried out on maize (Cochard, 2002a;Li, Sperry, & Shao, 2009;Ryu, Hwang, Kim, & Lee, 2016;Tyree, Fiscus, Wullschleger, & Dixon, 1986), sugarcane (Neufeld et al, 1992), sunflower (Ahmad et al, 2017;Cardoso, Brodribb, Lucani, DaMatta, & McAdam, 2018;Stiller & Sperry, 2002), and rice (Stiller et al, 2003;Stiller, Sperry, & Lafitte, 2005).…”
mentioning
confidence: 99%
“…Several studies have shown that this methodology is not prone to the open vessel artifact (Jacobsen & Pratt, 2012;Sperry et al, 2012;Hacke et al, 2014). Therefore, this technique was chosen because maximum vessel length of sunflower stems (23 cm; Ahmad et al, 2018) exceeded the sample length that was examined in this study. Fourteen-cm-long stem segments of well-watered sunflowers were cut under water and fixed in a custom-made centrifuge rotor (Sorvall RC-5C; Thermo Fisher Scientific, Waltman, MA, USA).…”
Section: Hydraulic Conductivity Lossmentioning
confidence: 99%